Subjetivando e objetivando: uma experiência de seleção para bolsa de estudos - Silva, Núbia Mara de Oliveira (2007)
The objective of this study is investigate the process of election for scholarship in two Philanthropic Universities and to reflect on the intersubjective aspects that are part of this process, as way to humanize the socioeconomic election. The sample was constituted by two groups of citizens, the first one was formed by 2 professionals who co-ordinate this activity in the Universities and the second one by 40 students who got philanthropic scholarship. From previous experience with scholarship we evidence that the intersubjective aspects must be part of the exercise of election, and when they are not observed they inhumanize the activity, because they simply fit the citizens in the criterion preset for concession of scholarship. The interview with the coordinating professionals allowed us to know the Scholarship Programs of the two Universities and evidences that, in general way, little visibility to the intersubjective aspects is given for fear to compromise the isonomy of the process. The evaluation of the scholarship holders on this problematic was gotten by means of an auto-inform questionnaire, being the data worked for punctuation average. For such, program SPSS - Statistical Package for the Social Sciences - was used as data base. From this evaluation, we identified that the way of the students become related with this activity is very peculiar, depending on the history of life of each one, its way to feel, to think and to act in the world. And, therefore, we verify that considering these aspects is essential to construct an election instrument that is not cold, thus disrespecting, the subjectivity of those ones who constitute it. It was evidenced that the art of listening and receiving in the interviews for scholarship are the entrance to humanize the process of scholarship election in the Universities